Linux in a nutshell - Siever, Ellen (In a nutshell (O'Reilly & Associates), 2003)
Linux in a Nutshell, now in its fourth edition, has won awards in the Linux community as the most indispensable book about Linux. It is an essential desktop reference for the commands that users of Linux utilize every day, with the depth of information and the practical, succinct "In a Nutshell" format that made the previous editions so popular. Comprehensive but concise, Linux in a Nutshell covers all substantial user, programming, administration, and networking commands for the most common Linux distributions. It's several quick references rolled into one: sed, gawk, RCS, CVS, vi, Emacs, bash, tcsh, regular expressions, package management, bootloaders, and desktop environments are all covered in this clear, to-the-point volume, along with core command-line utilities. The fourth edition continues to track the major changes in bootloaders, the GNOME and KDE desktops, and general Unix commands. Several commands related to CDs and music reflect the evolution of multimedia on Linux. Coverage has been added for GRUB, which has become the default bootloader on several Linux distributions, and for vim, the popular and feature-loaded extension to vi. The addition of several new options to the iptables firewall command and new commands related to DNSSEC and ssh show the book's value as a security tool. With this book, you no longer have to grope through long manpages and info documents for the information you need; you'll find it here in clear language and an easy-to-read format. Contents include: Programming, system administration, networking, and user commands with complete lists of options GRUB, LILO, and Loadlin bootloaders Shell syntax and variables for the bash, csh, and tcsh shells Pattern matching Emacs, vi, and vim editing commands sed and gawk commands The GNOME and KDE desktops and the fvwm2 window manager Red Hat and Debian package managers